Programming Fundamentals - A Modular Structured Approach using C++ - Busbee, Kenneth Leroy (Open textbook library., 2013)
Programming Fundamentals - A Modular Structured Approach using C++ is written by Kenneth Leroy Busbee, a faculty member at Houston Community College in Houston, Texas. The materials used in this textbook/collection were developed by the author and others as independent modules for publication within the Connexions environment. Programming fundamentals are often divided into three college courses: Modular/Structured, Object Oriented and Data Structures. This textbook/collection covers the first of those three courses. The learning modules of this textbook/collection were written as standalone modules. Students using a collection of modules as a textbook will usually view it contents by reading the modules sequentially as presented by the author of the collection. The learning modules of this textbook/collection were, for the most part, written without consideration of a speci??c programming language. In many cases the C++ language is discussed as part of the explanation of the concept. Often the examples used for C++ are exactly the same for the Java programming language. However, some modules were written speci??cally for the C++ programming language. This could not beavoided as the C++ language is used in conjunction with this textbook/collection by the author in teaching college courses.